2008
DOI: 10.1177/0961203307086509
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in the Fars Province of Iran

Abstract: Clinical features of systemic lupus erythematosus (SLE) have been described from different geographical regions in the world. However, data from many Middle East countries, including Iran, are scarce. This study aims to demonstrate the demographic, clinical, and laboratory characteristics in Iranian patients with SLE. In this prospective study, all the patients referring to Shiraz educational hospitals (Nemazi-Hafez) with SLE (American College of Rheumatology criteria) during a 5-year period (2001 to 2006) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 46 publications
9
29
6
Order By: Relevance
“…This study identified a lupus nephritis prevalence rate significantly higher than that reported in a previous study (48%) conducted in Fars province of Iran between 2001 and 2006 [17]. This comparison may be indicative of an alarming incremental pattern of nephritis in the Persian SLE population or of a more elaborate examination of patients in the current study.…”
Section: Discussion ___________________________contrasting
confidence: 52%
“…This study identified a lupus nephritis prevalence rate significantly higher than that reported in a previous study (48%) conducted in Fars province of Iran between 2001 and 2006 [17]. This comparison may be indicative of an alarming incremental pattern of nephritis in the Persian SLE population or of a more elaborate examination of patients in the current study.…”
Section: Discussion ___________________________contrasting
confidence: 52%
“…Tables 1 and 2 A systematic literature search was conducted using PubMed and Google Scholar databases and 'urticaria' and 'systemic lupus erythematosus' as keywords, covering a period from 1950 to 2015. In most of the studies CSU or chronic urticarial rash in patients with SLE was termed 'chronic urticaria' [18,124], 'urticaria' [19][20][21][22][23]27,54,56,[125][126][127][128][129][130][131], 'urticarial eruptions of varying duration' [73], 'hives' [28,30,132,133], 'non-vasculitic urticaria' [25], 'urticarial lesions' [134,135] and 'chronic urticaria-like lesions' [26,53]. We did not include in the table reports where information on urticaria as a cutaneous manifestation of SLE was not reported in the paper [34, 74,136,137].…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between CSU and UV was made only in some studies [25,35,53,55,57,58,124,138]. Many other studies had no clear differentiation between CSU and UV but the latter may have been termed 'vasculitis' [20,23,54,125,128,129], 'vasculitic rash' [139], 'dermal vasculitis' [28,133] or 'cutaneous vasculitis' [28,37,126,127,140] that allowed us to assume that most of the patients with urticarial rash in these studies are patients with CSU. Almost all authors in these studies used Gilliam and Sontheimer classification of SLE skin manifestations [32] that support this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies [44][45][46][47][48][49][50][51][52] studies were excluded because it was not possible to extract the exact numbers of syndromes and/or patients resulting positive for autoantibodies tested or because they were not relevant for the purpose of this review.. Four studies [53][54][55][56] were also excluded as they focused on other biomarkers than autoantibodies.…”
Section: Literature Search Strategy and Articles Retrievedmentioning
confidence: 99%